2010
DOI: 10.1177/0363546509359064
|View full text |Cite
|
Sign up to set email alerts
|

TightRope Versus Fiber Mesh Tape Augmentation of Acromioclavicular Joint Reconstruction

Abstract: TightRope augmentation of a Weaver-Dunn procedure could provide increased protection for AC joint reconstruction, allowing for earlier mobilization and more aggressive early rehabilitation. The potential clinical effect of additional tightening in the superoinferior direction beyond that of the native joint remains an issue for further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 12 publications
0
37
0
4
Order By: Relevance
“…Many of the described repair options offer biomechanically robust reconstructions; however, they often require multiple drill holes through the clavicle, which can create stress risers or result in suture cutout (or both). The TightRope device has been described both biomechanically [2][3][4][5] and clinically 6-8 as a viable reconstruction option requiring only a single drill hole through the clavicle; however, concerns over suture failure through bony cutout remain. Allograft augmentation of this fixation construct helps to eliminate the stress risers potentially created by the device while increasing overall repair construct stability.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many of the described repair options offer biomechanically robust reconstructions; however, they often require multiple drill holes through the clavicle, which can create stress risers or result in suture cutout (or both). The TightRope device has been described both biomechanically [2][3][4][5] and clinically 6-8 as a viable reconstruction option requiring only a single drill hole through the clavicle; however, concerns over suture failure through bony cutout remain. Allograft augmentation of this fixation construct helps to eliminate the stress risers potentially created by the device while increasing overall repair construct stability.…”
Section: Discussionmentioning
confidence: 99%
“…9 Several authors have evaluated the biomechanical properties of the TightRope system for AC joint reconstruction. [2][3][4][5] Most often, these studies have reported high vertical stiffness loads with the TightRope construct but more physiological axial stiffness with other techniques such as hook plates, bone anchors, and cerclage wires. 2,4 Similarly, clinical investigations have examined the clinical application of the TightRope device for AC joint reconstruction, with encouraging outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diese reduzieren aufgrund der transklavikulären und -korakoidalen Fixation die Gefahr eines Sägeeffektes des Nahtmaterials und eines anterioren "slippage" der Cerclage entlang der Korakoid-Krümmung [9,24]. Die maximale Belastbarkeit solcher Augmentationen erreicht dabei das Niveau des intakten AC-Gelenkes und die verbleibende horizontale Instabilität ist gegenüber der konventionellen CC-Cerclage reduziert [26], allerdings nicht auf das Niveau des intakten AC-Gelenkes. Als implantatspezifisches Problem stellte sich zudem die Lastkonzentration bei kleinflächigen Fixations-Buttons heraus, was in einem gewissen Prozentsatz der Patienten zum Einsinken der Buttons vor allem in den klavikulären Knochen führte.…”
Section: Korakoklavikuläre Rekonstruktionstechnikenunclassified
“…Die biomechanischen Ergebnisse dieser Techniken sind wahrscheinlich bedingt durch die unterschiedlichen Formen der CC-Augmentation inkonsistent. Letztendlich bildet aber auch für diese Techniken die posteriore AC-Gelenkstabilisierung eine nachgewiesene Schwachstelle [13,23,26].…”
Section: Introductionunclassified